Comparison of FIB‐4 and APRI in Chinese HBV‐infected patients with persistently normal ALT and mildly elevated ALT. Issue 4 (19th November 2012) - Wang, H.; Xue, L.; Yan, R.; Zhou, Y.; Wang, M. S.; Cheng, M. J.; Huang, H. J.
Summary Significant liver disease has been reported in chronic hepatitis B patients with normal alanine aminotransferase (ALT). Liver biopsy (LB) is the current gold standard for assessing hepatic inflammation and fibrosis in patients with chronic HBV. However, associated risks have led to the development of noninvasive models. Their utility in patients with normal ALT is unknown. FIB‐4 and aspartate aminotransferase (AST)‐to‐platelet ratio index (APRI) were calculated for patients with chronic HBV infection undergoing biopsy. The performance of each model and AUROC for predicting significant fibrosis (Scheuer's score ≥ S2) were determined for the entire cohort and stratified by elevated (≥50 U/L) and normal ALT. Two‐hundred and thirty‐one liver biopsies were included. The number of patient with normal ALT was 140, and 22.1% had significant fibrosis. The AUROC curve for patients with normal ALT was 0.81 for FIB‐4 and 0.80 for APRI, compared with 0.71 for FIB‐4 and 0.72 for APRI for those with mildly elevated ALT level. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of FIB‐4 were 0.63, 0.88, 0.61 and 0.93, for patients with normal ALT; the values for APRI were 0.40, 0.88, 0.33 and 0.93. Both FIB‐4 and APRI are useful for identification of those without significant fibrosis. However, because they have poor PPV, LB will continue to be used for assessment of HBV‐infected patients with normal ALT and mildly elevated ALT.